Localized immune tolerance from FasL-functionalized PLG scaffolds. (February 2019) - Skoumal, Michael; Woodward, Kyle B.; Zhao, Hong; Wang, Feng; Yolcu, Esma S.; Pearson, Ryan M.; Hughes, Kevin R.; García, Andrés J.; Shea, Lonnie D.; Shirwan, Haval
Abstract: Intraportal allogeneic islet transplantation has been demonstrated as a potential therapy for type 1 diabetes (T1D). The placement of islets into the liver and chronic immunosuppression to control rejection are two major limitations of islet transplantation. We hypothesize that localized immunomodulation with a novel form of FasL chimeric with streptavidin, SA-FasL, can provide protection and long-term function of islets at an extrahepatic site in the absence of chronic immunosuppression. Allogeneic islets modified with biotin and engineered to transiently display SA-FasL on their surface showed sustained survival following transplantation on microporous scaffolds into the peritoneal fat in combination with a short course (15 days) of rapamycin treatment. The challenges with modifying islets for clinical translation motivated the modification of scaffolds with SA-FasL as an off-the-shelf product. Poly (lactide-co-glycolide) (PLG) was conjugated with biotin and fabricated into particles and subsequently formed into microporous scaffolds to allow for rapid and efficient conjugation with SA-FasL. Biotinylated particles and scaffolds efficiently bound SA-FasL and induced apoptosis in cells expressing Fas receptor (FasR). Scaffolds functionalized with SA-FasL were subsequently seeded with allogeneic islets and transplanted into the peritoneal fat under the short-course of rapamycin treatment. Scaffolds modified with SA-FasL had robust engraftment of the transplanted islets that restored normoglycemia for 200 days. Transplantation without rapamycin or without SA-FasL did not support long-term survival and function. This work demonstrates that scaffolds functionalized with SA-FasL support allogeneic islet engraftment and long-term survival and function in an extrahepatic site in the absence of chronic immunosuppression with significant potential for clinical translation.